BYK-Chemie presents new additives; agrees clay additives deal with ITENE. Issue 2 (February 2015) - Unknown
Abstract : Germany's BYK-Chemie GmbH, part of the Altana group's BYK Additives & Instruments Division, has launched new additives for use in various fibre-reinforced plastics. SCONA TPPP 9212 FA/GA is designed for use in polypropylene (PP) compounds while BYK-P 9920 is particularly recommended for use in epoxy resin and vinyl ester composites.